A Minimum Spanning Forest Based Method for Noninvasive Cancer Detection with Hyperspectral Imaging - Pike, Robert (IEEE Trans Biomed Eng, 2015)
GOAL: The purpose of this paper is to develop a classification method that combines both spectral and spatial information for distinguishing cancer from healthy tissue on hyperspectral images in an animal model. METHODS: An automated algorithm based on a minimum spanning forest (MSF) and optimal band selection has been proposed to classify healthy and cancerous tissue on hyperspectral images. A support vector machine (SVM) classifier is trained to create a pixel-wise classification probability map of cancerous and healthy tissue. This map is then used to identify markers that are used to compute mutual information for a range of bands in the hyperspectral image and thus select the optimal bands. An MSF is finally grown to segment the image using spatial and spectral information. CONCLUSION: The MSF based method with automatically selected bands proved to be accurate in determining the tumor boundary on hyperspectral images. SIGNIFICANCE: Hyperspectral imaging combined with the proposed classification technique has the potential to provide a noninvasive tool for cancer detection.